Methodology for the identification of bioactive and marker peptides in the organs of cattle and pigs - D. V. Khvostov; N. L. Vostrikova; I. M. Chernukha (Теория и практика переработки мяса)
The development of general conception methodology for the meat-based functional food compositions is especially relevant today due to the growing consumers’ interest and attention to their health. This category of these food-products is intended for personal  ized nutrition of various age groups in the population, taking into account fortification of the food with nutraceuticals and with functional and metabolically active ingredients obtained from animal and vegetable source. Therefore, it was necessary to develop a certain tool for reliable identification of free peptides from the offals (by-products like hearts and aorta from Sus scrofa and Bos taurus) and from the ready-to-consume meat food (canned food) based on the free peptides, which food is potentially targeted to help with some issues in the human body. The authors proposed the methodology for identification of peptides weighing less than 5 kDa. This methodology has a row of significant advantages, such as a short time of analysis (90 minutes) and the possibility to prepare a large number of samples simultaneously (n=16). Analysis of bioactive peptides (BAPs) was performed by liquid chro  matography combined with time-of-flight mass spectrometry (Agilent 6545XT AdvanceBio LC/Q-TOF). The marker peptides were detected by a triple quadrupole mass spectrometer (Agilent 6410 Triple Quadrupole LC/MS). All peptide sequences were defined with the help of mass spectrometric data processing databases like PepBank, BioPep, AHTPDB. In this work from 39 to 269 peculiar soluble peptides were found, with an extraction level of 0.17–0.23%. The main fraction consisted of short peptides less than 1000 Da (71.0–98.0%). In experimental samples of pork hearts and arteries 7 peculiar marker peptides were identified. FFESFGDL  SNADAVMGNPK peptide obtained from the β-hemoglobin protein is of a special interest, as this peptide showed the maximum intensity of a signal. Presumably, this peptide can serve as an indicator of the blood presence in the finished food product. So it can serve as an assessment tool of bleeding degree of meat raw. For pork aortas a specific peptide TVLGNFAAFVQK was isolated from serum albumin, which turned out to be stable during heat treatment. This is also important for assessment of meat food that are subjected to high thermal exposure.